Literaturdidaktik - Leubner, Martin 1961-; Saupe, Anja 1963-; Richter, Matthias 1957- (De Gruyter Studium, 2016)
How can we impart a joy for reading to students while promoting their reading comprehension? This textbook offers a practical introduction to literary didactics and also develops an innovative competency model for reading comprehension. Several chapters have been completely revised for the new edition, with new chapters added on "writing" and "instructional units." - Lesen erweitert den Horizont. Lesen macht Spaß! Doch wie kann man das Lesen literarischer Texte lernen? Wie lassen sich Lesefreude und Lesemotivation im Literaturunterricht vermitteln, wie Lesekompetenz und Textverstehen gezielt fördern? Dieses